Back Cover: Direct Conversion of Mono‐ and Polysaccharides into 5‐Hydroxymethylfurfural Using Ionic‐Liquid Mixtures (ChemSusChem 16/2016). Issue 16 (23rd August 2016) - Siankevich, Sviatlana; Fei, Zhaofu; Scopelliti, Rosario; Jessop, Philip G.; Zhang, Jiaguang; Yan, Ning; Dyson, Paul J.
Abstract : The Back Cover picture represents the conversion of lignocellulose into the renewable building block HMF using a mixture of designer ionic liquids that work together in unison. More details can be found in the Full Paper by Siankevich et al. onpage 2089 in Issue 16, 2016 (DOI:10.1002/cssc.201600313 ).